PENGARUH CORPORATE GOVERNANCE TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR PERIODE SEBELUM DAN SELAMA COVID-19 - Syuza, Muhamad Raja; Prastiwi, Andri (Diponegoro Journal of Accounting, 2024)
This research was conducted to analyze the influence of corporate governance on the profit quality of manufacturing companies. The independent variables of this research are managerial ownership, independent board of commisioners, and audit committee. The dependent variable of this research is the quality of company profits. The population in this research is all manufacturing companies listed on the Indonesia Stock Exchange in 2018 – 2021. This research uses purposive sampling by taking samples based on certain criteria. With the existing criteria, a suitable sample of 193 was used. This research was conducted using mutiple linear regression analysis methods. The result of this research found that managerial ownership before and during the covid – 19 pandemic had no effect on earnings quality. The independent board of commisioners before the covid -19 pandemic had an effect on earnings quality. Whereas during the covid – 19 pandemic it had no effect on earnings quality. The audit committee before and during the covid – 19 pandemic affected earning quality.